2012
DOI: 10.1016/j.tvjl.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis due to Mycobacterium bovis and Mycobacterium caprae in sheep

Abstract: a b s t r a c tTuberculosis was diagnosed in three flocks of sheep in Galicia, Spain, in 2009 and 2010. Two flocks were infected with Mycobacterium bovis and one flock was infected with Mycobacterium caprae. Infection was confirmed by the comparative intradermal tuberculin test, bacteriology, molecular analysis and histopathology. Sheep have the potential to act as a reservoir for tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 10 publications
5
28
0
Order By: Relevance
“…Histopathology was typical of mycobacterial infection, but there was a distinct paucity of acid-fast bacteria seen on ZN-stained sections. This finding concurs with findings by others (Cordes and others 1981, Davidson and others 1981, Malone and others 2003, Marianelli and others 2010, Muñoz-Mendoza and others 2011). ZN smears of fresh tissues did not reveal any acid-fast organisms either.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Histopathology was typical of mycobacterial infection, but there was a distinct paucity of acid-fast bacteria seen on ZN-stained sections. This finding concurs with findings by others (Cordes and others 1981, Davidson and others 1981, Malone and others 2003, Marianelli and others 2010, Muñoz-Mendoza and others 2011). ZN smears of fresh tissues did not reveal any acid-fast organisms either.…”
Section: Discussionsupporting
confidence: 94%
“…Single cases (Houlihan and others 2008, Marianelli and others 2010) and flock outbreaks (Cordes and others 1981, Davidson and others 1981, Malone and others 2003, Muñoz Mendoza and others 2011) have been reported. M bovis infection was typically detected by the recognition of suspicious lesions at slaughter or at a diagnostic postmortem examination where the lesions have often been incidental findings (Cordes and others 1981, Houlihan and others 2008, Marianelli and others 2010, Muñoz Mendoza and others 2011, Tag el Din and others 1982). In two outbreaks, infected sheep were detected after skin testing of sheep in contact with tuberculous cattle (Davidson and others 1981, Malone and others 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As explained by different reports, including Radostits et al [36], as age increases the probability of acquiring TB infection increases. The result was in agreement with previous studies where sheep TB has been reported [35,[37][38][39]. Furthermore, in the multivariable logistic regression analysis, statistically significant difference was observed between goats and sheep.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in these areas there are reports of Iberian pigs infected with M. bovis with generalized lesions [54]. Reports of tuberculosis in sheep have been described in Italy [55] United Kingdom [56] and Spain [57] suggesting their potential to act as a reservoir for tuberculosis. The lack of data from these domestic species, together with the uncertainty regarding their role in bTB epidemiology in Spain made not possible to include them in the analysis.…”
Section: Discussionmentioning
confidence: 99%